2016
DOI: 10.1140/epja/i2016-16118-x
|View full text |Cite
|
Sign up to set email alerts
|

Probing nuclear bubble configuration by the $\pi^{-} / \pi^{+}$ ratio in heavy-ion collisions

Abstract: It is theoretically and experimentally argued that there may exist bubble or toroid-shaped configurations in some nucleus systems. Based on the isospin-dependent transport model of nucleus-nucleus collisions, here we propose a method to probe the bubble configuration in nucleus. That is, one could use the value of π − /π + ratio especially its kinetic energy distribution in head-on collision at intermediate energies to probe whether there is bubble configuration or not in projectile and target nuclei. Due to d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In this study, pion production in our used transport model is the same as that shown in [50] but without medium corrections of both elastic and inelastic baryon-baryon scattering cross sections. We use the Skyrme-type parametrization for the isoscalar mean field [51][52][53], i.e.…”
Section: The Methodology and Resultsmentioning
confidence: 99%
“…In this study, pion production in our used transport model is the same as that shown in [50] but without medium corrections of both elastic and inelastic baryon-baryon scattering cross sections. We use the Skyrme-type parametrization for the isoscalar mean field [51][52][53], i.e.…”
Section: The Methodology and Resultsmentioning
confidence: 99%
“…Recently, Stone et al have systematically studied the effects of the proton and neutron density distributions in central HIC, and found that the maximal neutron-to-proton ratio during the collision process is quite sensitive to the initial-state density distributions [19], where the different maximum neutron-to-proton ratios would result in a difference of π productions. Therefore, it was also shown recently that π mesons provide a remarkably good probe to study bubble structure inside nuclei [20]. On the surface of the nucleus, the density distributions of protons and neutrons of some nuclides were also obtained using x-ray and nuclear spectral analysis of antiprotons, respectively [21].…”
Section: Introductionmentioning
confidence: 99%